Design of Hand Sanitizing Device with Mist Spray Based On Microcontroller - Kusuma Afdhal, Thirafi Hadi; Puteri Novani, Nefy (CHIPSET, 2025)
The importance of hand washing habits as part of a healthy lifestyle is one of the basic hygiene practices that are effective in preventing the spread of disease and infection. In this study, the design and implementation of a hand sanitizer using a microcontroller-based disinfectant mist has been developed. The design of this system can be a solution to saving water when washing hands and increasing hand washing habits with the availability of this tool in public places. This tool uses a Passive Infrared (PIR) sensor to detect the presence of hands, then the mist maker will be active to produce mist from the sterilization fluid. The results obtained in this study indicate that the tool can detect hand movements with a range of 45˚ to 135˚. The mist maker produces mist at a rate of 183.323 ml/hour with a sterilization process of 15 seconds and converts 4.56 ml of liquid into mist when this tool is used. This tool is effective and efficient for use in public places.